Pengujian Aplikasi CRUD Dengan MySQL dan PHPMyAdmin - Erlangga; Iqbal firmansyah; M. Ali Topan Nugroho; Andri Rosandi; Aries Saifudin (CV. Multi Kreasi Media, 2024)
This time the examiner explains how to create a CRUD system in php. Test editor “sublime text”which will be the input for the experiment with the “XAMPP” web server as well as the “CHROME” webbrowser as the output of this test. And the PHPMyadmin application as the Mysql.